Peran Bahasa dalam Pembentukan Budaya Sasak: Perspektif Linguistik - Hasanuddin Chaer; Sukri Sukri; Mahmudi Efendi; Ade Jauhari (Universitas Hamzanwadi, 2026)
This research aims to understand the close relationship between language and culture as two elements that influence each other in social life, particularly in the Sasak community in Lombok. The Sasak language serves as a means of communication and a medium for conveying values, norms, and cultural identity from generation to generation. This research uses a literature study research method with the following steps: a. Collecting sources from journals; b. Books; c. Related documents; d. Analyzing articles in Indonesian and English; e. Reviewing cultural manuscripts, which were then summarized and analyzed using a linguistic approach. Theoretically, this research draws on the social linguistics perspective of Dell Hymes, which emphasizes the role of language in shaping and maintaining culture through social interaction. In addition to viewing language as a reflection of social reality and a cultural symbol with philosophical meaning, such as in the vocabulary of